Management Characteristics and Audit Opinion Shopping - Maryam Seifzadeh; Mahdi Salehi; Bizhan Abedini; Mohammad Hamed Khanmohammadi; Mohammad Hossein Ranjbar (Iranian Journal of Accounting, Auditing & Finance)
The present study assesses the relationship between management characteristics (management entrenchment, narcissism, CEO overconfidence, board effort, real and accrual-based earnings management) and audit opinion shopping in the Tehran Stock Exchange-listed firms. In other words, this paper seeks to answer the question "whether management characteristics can exert a favourable effect on audit opinion shopping or not." For this study, the multivariate regression model is used for hypothesis testing. Research hypotheses are examined using a sample of 1309 observations on the Tehran Stock Exchange during 2012-2018 and by employing the panel data-based multivariate regression and fixed-effects model. The results show a negative and significant relationship between management entrenchment and managers' overconfidence and audit opinion shopping. A positive and meaningful relationship was observed between management narcissism, real and accrual-based earnings management, and board effort and audit opinion shopping.